Reproducibility of Fruit Spirit Distillation Processes - Daniel Heller; Daniel Einfalt (Beverages, 2022)
Fruit spirit distillations processes are based on physical principles of heat and mass transfer. These principles are decisive for the separation of desired and undesired aroma compounds, which affect the quality of the distilled product. It is mandatory to control heat and mass transfer parameters to be able to perform fruit spirit distillation processes in a reproducible manner and to achieve equal products with similar volatile compound compositions repeatedly. Up to now, only limited information is available on the magnitude of reproducibility errors since fruit spirit distillation columns are typically not equipped with a suitable control or monitoring technique. We upgraded a batch distillation column with digitized instrumentation and a control technique to be able to control crucial parameters such as thermal energy inputs and reflux rates. This study aimed to identify whether control over two distillation parameters has the potential to enable us to perform distillation processes repeatedly. This study analyzed the magnitude of reproducibility errors for (i) six monitored distillation process parameters and (ii) 13 quantified volatile compounds in the product between duplicated distillation runs performed with equal setups. A total of eight different distillations were performed in duplicate (n = 16), while the six distillation parameters were monitored and logged every ten seconds. The produced distillates were equally subsampled into 20 fractions and each fraction analyzed for 13 volatile compound concentrations. Based on a dataset of 28,600 monitored duplicate distillation process data points, this study showed that process parameters can indeed be replicated with a median relative standard deviation (RSD) of <0.1% to 7% when two crucial process parameters are controlled. The comparison of 1540 volatile compound concentrations in the product fractions showed a reproducibility error with an average median RSD of 9 ± 8%. This illustrated that by gaining control over thermal energy input and reflux rates, the reproducibility of fruit spirit distillation processes and their associated products can largely be met. It is advisable to equip distillation columns with a suitable control technique to be able to reproduce the performance of fruit spirit distillations.